"Ruled Britannia": Metaphorical Construction of the EU as Enemy in UKIP Campaign Posters. (January 2021) - Ross, Andrew S.; Bhatia, Aditi
The sweeping tide of populism across the globe has given rise to isolationist sentiments that call for the closing of national borders and a return to nativist roots. This has been most evident in Britain in terms of the controversial vote to exit the European Union (EU) during the 2016 referendum (to Leave or Remain) and more recently with the lead up to a general election and mounting pressure on the government to implement an exit strategy. The most vocal proponent of the "leave" movement was the United Kingdom Independence Party (UKIP), reframing the debate on EU membership in terms of invasion and oppression. This paper focuses on precisely this discursive construction of the EU by analyzing UKIP campaign posters through application of Bhatia's Discourse of Illusion framework on three levels: historicity (use of the past to justify the present or predict the future), linguistic and semiotic action (subjective conceptualizations of reality made apparent through metaphorical rhetoric), and degree of social impact (emergence of delineating categories through ideological narrative).